The Effect of Social Support on Student Academic Stress (Case Study Department of Economic Education Unima) - Siswanto, Sri Purwaningsih (International Journal of Curriculum Development, Teaching and Learning Innovation, 2023)
This study aims to determine whether there is an influence of social support on academic stress in students majoring in economic education . This research approach is a quantitative approach to the type of correlational research. The population in this study is whole student in majoring in economic education as much 1 023 . Research sample as much 21 3 coed students who taken using simple random sampling technique . The data collection tool uses a scale of social support adapted from Multidimensional Scale of Perceived Social Support (MSPSS) and academic stress scale adapted from Perceptions of Academic Stress (PAS) Scales . Data analysis technique using simple regression analysis. Based on the results of simple regression analysis, the coefficient value is obtained regression social support as big 0.067 2 _ with level significance as big 0.0 89 < 0.05. Besides That mark t count as big 2,062 > t table of 1.10 8 . Matter it can be concluded that variable X (social support) has an effect on variable Y (academic stress), which means there is influence positive support social to stress academic great student in the Department of Economic Education UNIMA.